Application of a small-timescale fatigue, crack-growth model to the plane stress/strain transition in predicting the lifetime of a tunnel-boring-machine cutter head. (January 2017) - Huo, Junzhou; Zhu, Dong; Hou, Nan; Sun, Wei; Dong, Jianghui
Abstract: The crack-growth lifetime of a tunnel-boring-machine (TBM) cutter head accounts for more than 80% of a TBM cutter head's entire lifetime. Considering the ultrathick plate of a TBM cutter head, a small-timescale crack-growth model is modified to predict crack-growth lifetime based on the plane stress/strain transition condition. An improved quasistatic method is proposed to calculate the dynamic stress of the weak points of the cutter head, which is used as the input load. A plastic constraint factor α is introduced to change the yield stress value of the material. The transition of the stress/strain state in the crack tip is simulated, and the modified model is verified by a fatigue crack-growth test of the characteristic substructure, giving better prediction results. Finally, this method is applied to predict the crack-growth lifetime of a TBM cutter head in the Water Diversion Project in Northwest Liaoning Province, China, and the results show that when the crack of the cutter head's vulnerable part grows from 0.1 mm to 60 mm in depth, the TBM's useful driving distance is about 11.2 km. Highlights: An improved quasi-static method was proposed to calculate the dynamic stress of the cutter head and verified. A plastic constraint factor α was introduced to change the yield stress value of material. A small-timescale fatigue crack growth model of plane stress/strain transition was proposed and applied in TBM cutter head. The crack growth life of TBM cutter head in the Liaoning northwest water diversion project was predicted in this paper.